Decorative-formative and spatial organization of representative architecture 1930s − early 1950s as a reflection of the state-ideological goal - Bachynska, Liudmyla (КНУБА, 2018)
Consequently, the architectural and urban heritage frankly reflected the true manifestations of the state-ideological goal of countries with totalitarian political regimes. The architectural legacy of European states significantly differed from that of the USSR by the fact that European states frankly proclaimed the ambition of their own political programs, and the Soviet state with the help of architectural means created an idyll of peacefulness and a bright future.
Keywords: the architecture; the political regime; the state symbols; the form and style of architecture.; 72.036"1930/1950"